Optimal technique, variability, control, and skilled performance - Yeadon, M. R.; Hiley, M. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
Optimisation is often used in an attempt to explain technique adopted in skilled sport performance. This might take the form of minimising joint torques in an expectation that the optimum simulated technique will resemble the actual performance. If a suitable optimisation criterion can be identified then this may give some insight into the adopted technique. In all human movement there is inherent variation so that no two performances are exactly the same. As a consequence skilled technique needs to be successful in a noisy environment and so optimised technique also needs to be robust to the inherent variation in coordination. In movements in which there is sufficient time for feedback control to operate it is to be expected that there will be greater variation in technique in those phases that adjustments are made. It is also to be expected that there will be little variation in technique for those phases where accurate coordination is crucial to the success of the movement. The aspect that often governs elite technique is that of achieving consistent success rather than some biomechanical measure of movement.